Dicarbonyl stress in clinical obesity - Masania, Jinit (Glycoconj J, 2016)
The glyoxalase system in the cytoplasm of cells provides the primary defence against glycation by methylglyoxal catalysing its metabolism to D-lactate. Methylglyoxal is the precursor of the major quantitative advanced glycation endproducts in physiological systems - arginine-derived hydroimidazolones and deoxyguanosine-derived imidazopurinones. Glyoxalase 1 of the glyoxalase system was linked to anthropometric measurements of obesity in human subjects and to body weight in strains of mice. Recent conference reports described increased weight gain on high fat diet-fed mouse with lifelong deficiency of glyoxalase 1 deficiency, compared to wild-type controls, and decreased weight gain in glyoxalase 1-overexpressing transgenic mice, suggesting a functional role of glyoxalase 1 and dicarbonyl stress in obesity. Increased methylglyoxal, dicarbonyl stress, in white adipose tissue and liver may be a mediator of obesity and insulin resistance and thereby a risk factor for development of type 2 diabetes and non-alcoholic fatty liver disease. Increased methylglyoxal formation from glyceroneogenesis on adipose tissue and liver and decreased glyoxalase 1 activity in obesity likely drives dicarbonyl stress in white adipose tissue increasing the dicarbonyl proteome and related dysfunction. The clinical significance will likely emerge from on-going clinical evaluation of inducers of glyoxalase 1 expression in overweight and obese subjects. Increased transcapillary escape rate of albumin and increased total body interstitial fluid volume in obesity likely makes levels of glycation of plasma protein unreliable indicators of glycation status in obesity as there is a shift of albumin dwell time from plasma to interstitial fluid, which decreases overall glycation for a given glycemic exposure.